High-hardness low-density ceramic alloy material for paving and welding surface of workover tool and manufacturing method of high-hardness low-density ceramic alloy material

By adopting polyprism ceramic alloy particles and soft metal sintering methods, the problem of low grinding efficiency of surface welding materials of existing well repair tools is solved, and the development of high-hardness and low-density ceramic alloy materials is realized, which significantly improves grinding and milling Performance and efficiency reduce costs and production cycles.

CN119464816APending Publication Date: 2025-02-18CHINA NAT PETROLEUM CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310999209.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The grinding and milling efficiency of the surface welding materials of existing well repair tools is low, which cannot meet the grinding and milling needs of high-strength casing/oil pipes. In addition, traditional metal materials have high costs, low strength and complex processing, resulting in long production cycles and poor reliability.

Method used

The high-hardness and low-density ceramic alloy materials are obtained by sintering polyprism ceramic alloy particles and soft metals. The ceramic alloy particles include WC, TiC, NbC, VC, Co, Ni, and the soft metal is Cu–Ni-Ti-Zn-type material powder. Improve grinding and milling performance and efficiency by optimizing composition and sintering process.

Benefits of technology

It significantly improves the grinding and milling performance and grinding efficiency of well repair tools, reduces production costs, improves the hardness and reliability of materials, shortens the production cycle and simplifies the processing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004385819800000101
    Figure BDA0004385819800000101
Patent Text Reader

Abstract

The invention provides a high-hardness and low-density ceramic alloy material for paving and welding the surface of a workover tool and a manufacturing method thereof, the high-hardness and low-density ceramic alloy material is obtained by sintering polygonal ceramic alloy particles and soft metal, the polygonal ceramic alloy particles are formed by compositely sintering WC, TiC, NbC, VC, Co and Ni, and due to the fact that the adopted TiC material is a very hard ceramic material, the high-hardness and low-density ceramic alloy material has excellent wear resistance, and the service life of the high-hardness and low-density ceramic alloy material is prolonged. And the stable performance is kept in a high-temperature environment, the density is about 50 wt% of that of a traditional WC material, the use amount of a laying welding alloy material can be greatly reduced, the hardness and laying welding performance of the ceramic alloy material are improved, and meanwhile the material manufacturing cost is greatly reduced. Meanwhile, Cu-Ni-Ti-Zn series powder is adopted as the soft metal material, the components and proportion of the soft metal material are reasonably matched, the strength, wear resistance and weldability of the soft metal material are improved, the milling performance and milling efficiency of the milling tool are effectively improved, and then the milling capacity of the milling tool on the steel pipe is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of well repair tool manufacturing in the petroleum and natural gas industry, and relates to a high-hardness and low-density ceramic alloy material for surface welding of well repair tools and a manufacturing method thereof. Background Art

[0002] TiC is a very hard ceramic material with many excellent properties and application characteristics. TiC has a very high hardness, close to diamond (about 90wt% hardness of diamond), and is therefore second only to diamond in hardness. This gives TiC excellent wear resistance and makes it suitable for applications under various high wear and high friction conditions. At the same time, TiC has a high melting point, which enables it to maintain stable performance in high temperature environments. TiC has good thermal conductivity, which enables it to effectively transfer heat and is suitable for high temperature applications and occasions with high heat dissipation requirements. In addition, TiC has a relatively low density, which gives it an advantage in some lightweight applications.

[0003] In the process of drilling and oil and gas, as the depth of the oil well increases, a large number of high-strength casing / tubings are needed. The strength and performance of casing / tubings are related to the safety and reliability of gas extraction, which further puts forward higher requirements on the grinding performance and efficiency of well repair tools. At present, the grinding efficiency of the surface of well repair grinding tools with WC particles welded is low and can no longer meet the needs of on-site operations. It is urgent to develop hard alloy materials with higher grinding efficiency and performance for high-strength casing / tubings.

[0004] At present, some welding metal materials are used to weld a layer on the surface of the milling tool to improve the milling performance and efficiency of the milling tool. However, the cost of traditional welding metal materials is high, which may lead to an increase in the price of well repair tools. In the case of impact or severe vibration, the strength is low and it may be easy to break or damage, which reduces the reliability of the well repair tools. In addition, the processing of metal materials is relatively complex, and the manufacturing process may be cumbersome, resulting in a long production cycle. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a high-hardness and low-density ceramic alloy material for surface welding of well repair tools and a manufacturing method thereof, which effectively improves the grinding performance and grinding efficiency of the grinding tools, reduces the production cost, improves the strength, increases the reliability of the well repair tools, shortens the production cycle and simplifies the processing technology.

[0006] The present invention is achieved through the following technical solutions:

[0007] A high-hardness, low-density ceramic alloy material for surface welding of well repair tools, obtained by sintering ceramic alloy particles and soft metal, wherein the ceramic alloy particles account for 50wt%-60wt% and the soft metal accounts for 40wt%-50wt%;

[0008] The ceramic alloy particles include WC: 15wt%-20wt%, TiC: 45wt%-55wt%, NbC: 5wt%-8wt%, VC: 1wt%-3wt%, Co: 5wt%-10wt%, Ni: 4wt%-19wt%; the ceramic alloy particles are a polyhedral structure;

[0009] The soft metal is a Cu-Ni-Ti-Zn material powder, including Cu: 35wt%-45wt%, Ni: 30wt%-45wt%, Ti: 4wt%-7wt%, and the rest is Zn.

[0010] A method for manufacturing a high-hardness, low-density ceramic alloy material for surface welding of well repair tools, comprising:

[0011] S1, mixing TiC, NbC, VC and Ni powders in proportion in an oxygen-free environment so that the Ni powder is coated around the TiC powder, and then adding WC and Co powders and mixing in an oxygen-free environment to obtain a ceramic alloy powder;

[0012] S2, pressing the ceramic alloy powder into a shape, and sintering at a high temperature in a vacuum environment to obtain a sintered ceramic alloy material;

[0013] S3, crushing the sintered ceramic alloy material to obtain polygonal ceramic alloy particles;

[0014] S4, the polygonal ceramic alloy particles are mixed with soft metal and loaded into a mold, heated to 1200±50°C in an oxygen-free environment, kept warm for 10-15 minutes, and air-cooled to room temperature to obtain a high-hardness and low-density ceramic alloy material for surface welding of well repair tools.

[0015] Preferably, the particle size of the TiC, NbC, VC and Ni powders is 50 mesh to 300 mesh.

[0016] Preferably, the particle size of the WC and Co powders is 50-300 mesh.

[0017] Preferably, the die for compacting the ceramic alloy powder has a cylindrical or rectangular structure.

[0018] Preferably, the sintered ceramic alloy material is crushed and sieved into polygonal ceramic alloy particles of different specifications.

[0019] Preferably, the polygonal ceramic alloy particles of different specifications include alloy particles of specifications of 1mm-3mm, 3mm-5mm and 5mm-7mm.

[0020] Preferably, the mold in S4 is a cylindrical mold with a diameter of 8mm-20mm.

[0021] Preferably, the hardness of the polygonal ceramic alloy particles is HV1800-HV2000.

[0022] Preferably, the sintering temperature in S3 is 1600±50° C., the sintering time is 8h±1h, and the furnace is cooled.

[0023] Compared with the prior art, the present invention has the following beneficial technical effects:

[0024] The present invention proposes a high-hardness, low-density ceramic alloy material for surface welding of well repair tools and a manufacturing method thereof based on TiC ceramics with excellent cutting performance. The material is obtained by sintering polygonal ceramic alloy particles and soft metals, wherein the polygonal ceramic alloy particles are sintered by composite sintering of WC, TiC, NbC, VC, Co, and Ni. Since the TiC material used is a very hard ceramic material, it has excellent wear resistance, maintains stable performance under high temperature environment, and has a density of about 50wt% of traditional WC materials, which can greatly reduce the amount of welding alloy materials used. By optimizing the composition and ratio of the ceramic alloy material, the hardness and welding performance of the ceramic alloy material are improved, and the material manufacturing cost is greatly reduced. At the same time, the soft metal material adopts Cu-Ni-Ti-Zn powder, and the composition and ratio of the soft metal material are reasonably proportioned to improve the strength, wear resistance and weldability of the soft metal itself, effectively improve the grinding performance and efficiency of the grinding tool, and thus improve its ability to grind steel pipes;

[0025] The present invention also provides a method for manufacturing high-hardness and low-density ceramic alloy materials for surface welding of well repair tools. Large pieces of ceramic alloy are mechanically crushed to obtain small polygonal ceramic alloy particles. Air cooling is used to greatly improve the manufacturing efficiency of the ceramic alloy particles, thereby significantly reducing material costs. Soft metal materials use Cu-Ni-Ti-Zn powders and are sintered in an oxygen-free environment to avoid oxidation during the manufacturing process, thereby improving the density of the final ceramic alloy material. The hardness and grinding efficiency of the ceramic alloy material can be effectively improved, the manufacturing cost can be reduced, the production cycle can be shortened, and the processing technology can be simplified. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0027] (1) The material of the present invention is obtained by sintering polygonal ceramic alloy particles and soft metal, wherein the ceramic alloy particles account for 50-60wt% and the soft metal accounts for 40-50wt%. The polygonal ceramic alloy particles have the following components: WC: 15-20wt%, TiC: 45-55wt%, NbC: 5-8wt%, VC: 1-3wt%, Co: 5-10wt%, Ni: 4-19wt%. The soft metal is a Cu-Ni-Ti-Zn material powder, which has the following components: Cu: 35-45wt%, Ni: 30-45wt%, Ti: 4-7wt%, and the rest is Zn.

[0028] (2) First, TiC, NbC, VC and Ni powders with a particle size of 50-300 mesh are mixed uniformly in a certain proportion in an anaerobic environment so that the Ni powder is evenly coated around the TiC powder. Then, an appropriate amount of WC and Co powders with a particle size of 50-300 mesh are added to the mixed powder and mixed uniformly in an anaerobic environment to form a powder composition of WC: 15-20wt%, TiC: 45-55wt%, NbC: 5-8wt%, VC: 1-3wt%, Co: 5-10wt%, and Ni: 4-19wt%.

[0029] (3) The uniformly mixed ceramic alloy powder is pressed into a mold. The mold can be in the shape of a cylinder or a cuboid, and the size of the mold is selected according to the equipment capacity.

[0030] (4) The pressed ceramic alloy material is sintered at high temperature in a vacuum environment, the sintering temperature is 1600±50°C, and the sintering time is 8h±1h.

[0031] (5) The sintered ceramic alloy material is cooled to room temperature in the furnace, and the hardness of the alloy material is HV1800-HV2000.

[0032] (6) The sintered ceramic alloy material is mechanically crushed to obtain polygonal ceramic alloy particles with a size of 1 mm-7 mm, and then classified and screened according to three specifications of 1 mm-3 mm, 3 mm-5 mm and 5 mm-7 mm.

[0033] (7) According to the needs, select one of the specifications of ceramic alloy particles of 1mm-3mm, 3mm-5mm or 5mm-7mm and mix them evenly with the soft metal powder.

[0034] (8) It should be further explained that the proportion of ceramic alloy particles is 50-60wt%, and the proportion of soft metal powder is 40-50wt%.

[0035] (9) It should be further explained that the soft metal powder composition is Cu: 35-50wt%, Ni: 30-45wt%, Ti: 4-7wt%, and the rest is Zn, and the particle size is 50 mesh-300 mesh.

[0036] (10) The mixed alloy material is placed into a cylindrical mold with a diameter of 8 mm to 20 mm, and ensure that the soft metal powder is completely coated around the ceramic alloy particles.

[0037] (11) Place the mold filled with alloy material in an oxygen-free environment heating furnace and heat to 1200±50℃ for 10-15 minutes;

[0038] (12) The heated ceramic alloy rod is air-cooled to room temperature and taken out from the mold to obtain the finished product.

[0039] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0040] Embodiment 1:

[0041] (1) The sintered welding rod of the present invention is obtained by sintering polygonal sintered ceramic particles and soft metal, wherein the ceramic particles account for 50wt% and the soft metal accounts for 50wt%. The composition of the polygonal sintered hard alloy particles is WC: 15wt%, TiC: 45wt%, NbC: 5wt%, VC: 1wt%, Co: 5wt%, Ni: 19wt%. The soft metal is a Cu-Ni-Ti-Zn system material powder, wherein the composition is Cu: 35wt%, Ni: 30wt%, Ti: 4wt%, and the rest is Zn.

[0042] (2) First, TiC, NbC, VC and Ni powders with a particle size of 50-300 mesh are mixed evenly in a certain proportion in an anaerobic environment, and Ni powder is evenly coated around the TiC powder. Then, an appropriate amount of WC and Co powders with a particle size of 50-300 mesh are added to the mixed powder and mixed evenly in an anaerobic environment. The formed powder ratio is WC: 15wt%, TiC: 45wt%, NbC: 5wt%, VC: 1wt%, Co: 5wt%, Ni: 19wt%.

[0043] (3) pressing the uniformly mixed ceramic alloy powder into a rectangular parallelepiped mold;

[0044] (4) The pressed ceramic alloy material is sintered at high temperature in a vacuum environment at a sintering temperature of 1600°C and a holding time of 8 hours;

[0045] (5) The sintered ceramic alloy material is cooled to room temperature in the furnace, and the hardness of the alloy material is HV1800-HV1900.

[0046] (6) The sintered ceramic alloy material is mechanically crushed to obtain polygonal ceramic alloy particles with a size of 1 mm-7 mm, and then classified and screened according to three specifications of 1 mm-3 mm, 3 mm-5 mm and 5 mm-7 mm.

[0047] (7) Select ceramic alloy particles with a size of 1mm-3mm and mix them evenly with soft metal powder.

[0048] (8) It should be further explained that the proportion of the ceramic alloy particles is 50wt% and the proportion of the soft metal powder is 50wt%.

[0049] (9) It should be further explained that the soft metal components are Cu: 35wt%, Ni: 30wt%, Ti: 4wt%, and the rest is Zn, and the particle size is 50 mesh-300 mesh.

[0050] (10) The mixed alloy material is placed into a cylindrical mold with a diameter of 8 mm to 10 mm, and ensure that the soft metal powder is completely coated around the ceramic alloy particles.

[0051] (11) Place the mold filled with the mixed material in an oxygen-free environment heating furnace and heat it to 1200° C. for 10-15 minutes;

[0052] (12) The heated ceramic alloy rod is air-cooled to room temperature and taken out from the mold to obtain a finished product of a high-hardness, low-density ceramic alloy material for surface welding of well repair tools.

[0053] Embodiment 2:

[0054] (1) The sintered welding rod of the present invention is obtained by sintering polygonal sintered ceramic particles and soft metal, wherein the ceramic particles account for 60wt% and the soft metal accounts for 40wt%. The polygonal sintered ceramic particles have the composition of WC: 20wt%, TiC: 55wt%, NbC: 8wt%, VC: 3wt%, Co: 10wt%, Ni: 4wt%. The soft metal is a Cu-Ni-Ti-Zn system material powder, which has the composition of Cu: 45wt%, Ni: 45wt%, Ti: 7wt%, and the rest is Zn.

[0055] (2) First, TiC, NbC, VC and Ni powders with a particle size of 50-300 mesh are mixed evenly in a certain proportion in an anaerobic environment, and Ni powder is evenly coated around the TiC powder. Then, an appropriate amount of WC and Co powders with a particle size of 50-300 mesh are added to the mixed powder and mixed evenly in an anaerobic environment. The formed powder ratio is WC: 20wt%, TiC: 55wt%, NbC: 8wt%, VC: 3wt%, Co: 10wt%, and Ni: 4wt%.

[0056] (3) pressing the uniformly mixed ceramic alloy powder into a cylindrical mold;

[0057] (4) The pressed ceramic alloy material is sintered at high temperature in a vacuum environment at a sintering temperature of 1550°C and a holding time of 7 hours;

[0058] (5) The sintered ceramic alloy material is cooled to room temperature in the furnace, and the hardness of the alloy material is HV1900-HV2000.

[0059] (6) The sintered ceramic alloy material is mechanically crushed to obtain polygonal ceramic alloy particles with a size of 1 mm-7 mm, and then classified and screened according to three specifications of 1 mm-3 mm, 3 mm-5 mm and 5 mm-7 mm.

[0060] (7) Select ceramic alloy particles of 3mm-5mm in size and mix them evenly with soft metal powder.

[0061] (8) It should be further explained that the proportion of the ceramic alloy particles is 60wt% and the proportion of the soft metal powder is 40wt%.

[0062] (9) It should be further explained that the soft metal components are Cu: 45wt%, Ni: 45wt%, Ti: 7wt%, and the rest is Zn, and the particle size is 50 mesh-300 mesh.

[0063] (10) The mixed alloy material is placed into a cylindrical mold with a diameter of 14 mm to 16 mm, and ensure that the soft metal powder is completely coated around the ceramic alloy particles.

[0064] (11) Place the mold filled with the mixed material in an oxygen-free environment heating furnace and heat it to 1150° C. for 10-13 minutes;

[0065] (12) The heated ceramic alloy rod is air-cooled to room temperature and taken out from the mold to obtain a finished product of a high-hardness, low-density ceramic alloy material for surface welding of well repair tools.

[0066] Embodiment 3:

[0067] (1) The sintered welding rod of the present invention is obtained by sintering polygonal sintered ceramic particles and soft metal, wherein the ceramic particles account for 55wt% and the soft metal accounts for 45wt%. The composition of the polygonal sintered ceramic particles is WC: 17wt%, TiC: 50wt%, NbC: 7wt%, VC: 2wt%, Co: 8wt%, Ni: 16wt%. The soft metal is a Cu-Ni-Ti-Zn system material powder, wherein the composition is Cu: 40wt%, Ni: 40wt%, Ti: 4wt%, and the rest is Zn.

[0068] (2) First, TiC, NbC, VC and Ni powders with a particle size of 50-300 mesh are mixed evenly in a certain proportion in an anaerobic environment, and Ni powder is evenly coated around the TiC powder. Then, an appropriate amount of WC and Co powders with a particle size of 50-300 mesh are added to the mixed powder and mixed evenly in an anaerobic environment. The formed powder ratio is WC: 17wt%, TiC: 50wt%, NbC: 7wt%, VC: 2wt%, Co: 8wt%, and Ni: 16wt%.

[0069] (3) pressing the uniformly mixed ceramic alloy powder into a rectangular parallelepiped mold;

[0070] (4) The pressed ceramic alloy material is sintered at high temperature in a vacuum environment at a sintering temperature of 1650°C and a holding time of 9 hours;

[0071] (5) The sintered ceramic alloy material is cooled to room temperature in the furnace, and the hardness of the alloy material is HV1870-HV1940.

[0072] (6) The sintered ceramic alloy material is mechanically crushed to obtain polygonal ceramic alloy particles with a size of 1 mm-7 mm, and then classified and screened according to three specifications of 1 mm-3 mm, 3 mm-5 mm and 5 mm-7 mm.

[0073] (7) Select ceramic alloy particles of 5mm-7mm in size and mix them evenly with soft metal powder.

[0074] (8) It should be further explained that the proportion of the ceramic alloy particles is 55wt% and the proportion of the soft metal powder is 45wt%.

[0075] (9) It should be further explained that the soft metal components are Cu: 40wt%, Ni: 40wt%, Ti: 4wt%, and the rest is Zn, and the particle size is 50 mesh-300 mesh.

[0076] (10) The mixed alloy material is placed into a cylindrical mold with a diameter of 18 mm to 20 mm, and ensure that the soft metal powder is completely coated around the ceramic alloy particles.

[0077] (11) Place the mold filled with the mixed material in an oxygen-free environment heating furnace and heat it to 1250° C. for 13-15 minutes;

[0078] (12) The heated ceramic alloy rod is air-cooled to room temperature and taken out from the mold to obtain a finished product of a high-hardness, low-density ceramic alloy material for surface welding of well repair tools.

[0079] Example 4

[0080] (1) The sintered welding rod of the present invention is obtained by sintering polygonal sintered ceramic particles and soft metal, wherein the ceramic particles account for 52wt% and the soft metal accounts for 48wt%. The polygonal sintered ceramic particles have the composition of WC: 15wt%, TiC: 55wt%, NbC: 6wt%, VC: 2wt%, Co: 9wt%, Ni: 13wt%. The soft metal is a Cu-Ni-Ti-Zn system material powder, which has the composition of Cu: 40wt%, Ni: 45wt%, Ti: 5wt%, and the rest is Zn.

[0081] (2) First, TiC, NbC, VC and Ni powders with a particle size of 50-300 mesh are mixed evenly in a certain proportion in an anaerobic environment, and the Ni powder is evenly coated around the TiC powder. Then, an appropriate amount of WC and Co powders with a particle size of 50-300 mesh are added to the mixed powder and mixed evenly in an anaerobic environment. The formed powder ratio is WC: 15wt%, TiC: 55wt%, NbC: 6wt%, VC: 2wt%, Co: 9wt%, Ni: 13wt%.

[0082] (3) pressing the uniformly mixed ceramic alloy powder into a mold, wherein the mold is cylindrical or rectangular;

[0083] (4) The pressed ceramic alloy material is sintered at high temperature in a vacuum environment at a sintering temperature of 1620°C and a holding time of 8.5 hours;

[0084] (5) The sintered ceramic alloy material is cooled to room temperature in the furnace, and the hardness of the alloy material is HV1920-HV1980.

[0085] (6) The sintered ceramic alloy material is mechanically crushed to obtain polygonal ceramic alloy particles with a size of 1 mm-7 mm, and then classified and screened according to three specifications of 1 mm-3 mm, 3 mm-5 mm and 5 mm-7 mm.

[0086] (7) Select ceramic alloy particles of 3mm-5mm in size and mix them evenly with soft metal powder.

[0087] (8) It should be further explained that the proportion of ceramic alloy particles is 52wt% and the proportion of soft metal powder is 48wt%.

[0088] (9) It should be further explained that the soft metal components are Cu: 40wt%, Ni: 45wt%, Ti: 5wt%, and the rest is Zn, and the particle size is 50 mesh-300 mesh.

[0089] (10) The mixed alloy material is placed into a cylindrical mold with a diameter of 18 mm to 20 mm, and ensure that the soft metal powder is completely coated around the ceramic alloy particles.

[0090] (11) Place the mold filled with the mixed material in an oxygen-free environment heating furnace and heat it to 1250° C. for 11-14 minutes;

[0091] (12) The heated ceramic alloy rod is air-cooled to room temperature and taken out from the mold to obtain a finished product of a high-hardness, low-density ceramic alloy material for surface welding of well repair tools.

[0092] Table 1 Welding rod material composition and mass percentage

[0093]

[0094] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0095] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as shown in the specification and described above. However, any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A high-hardness, low-density ceramic alloy material for surface welding of well repair tools, characterized in that: Obtained by sintering ceramic alloy particles and soft metal, wherein the ceramic alloy particles account for 50wt%-60wt% and the soft metal accounts for 40wt%-50wt%; The ceramic alloy particles include WC: 15wt%-20wt%, TiC: 45wt%-55wt%, NbC: 5wt%-8wt%, VC: 1wt%-3wt%, Co: 5wt%-10wt%, Ni: 4wt%-19wt%; the ceramic alloy particles are a polyhedral structure; The soft metal is a Cu-Ni-Ti-Zn material powder, including Cu: 35wt%-45wt%, Ni: 30wt%-45wt%, Ti: 4wt%-7wt%, and the rest is Zn.

2. The method for manufacturing a high-hardness, low-density ceramic alloy material for surface welding of well repair tools according to claim 1, characterized in that: include, S1, mixing TiC, NbC, VC and Ni powders in proportion in an oxygen-free environment so that the Ni powder is coated around the TiC powder, and then adding WC and Co powders and mixing in an oxygen-free environment to obtain a ceramic alloy powder; S2, pressing the ceramic alloy powder into a shape, and sintering at a high temperature in a vacuum environment to obtain a sintered ceramic alloy material; S3, crushing the sintered ceramic alloy material to obtain polygonal ceramic alloy particles; S4, the polygonal ceramic alloy particles are mixed with soft metal and loaded into a mold, heated to 1200±50°C in an oxygen-free environment, kept warm for 10-15 minutes, and air-cooled to room temperature to obtain a high-hardness and low-density ceramic alloy material for surface welding of well repair tools.

3. The method for manufacturing a high-hardness, low-density ceramic alloy material for surface welding of well repair tools according to claim 2, characterized in that: The particle sizes of the TiC, NbC, VC and Ni powders are all between 50 meshes and 300 meshes.

4. The method for manufacturing a high-hardness, low-density ceramic alloy material for surface welding of well repair tools according to claim 2, characterized in that: The particle sizes of the WC and Co powders are both 50-300 meshes.

5. The method for manufacturing a high-hardness, low-density ceramic alloy material for surface welding of well repair tools according to claim 2, characterized in that: The die for compacting the ceramic alloy powder adopts a cylindrical or rectangular structure.

6. The method for manufacturing a high-hardness, low-density ceramic alloy material for surface welding of well repair tools according to claim 2, characterized in that: After the sintered ceramic alloy material is crushed, it is screened into polygonal ceramic alloy particles of different specifications.

7. The method for manufacturing a high-hardness, low-density ceramic alloy material for surface welding of well repair tools according to claim 6, characterized in that: The polygonal ceramic alloy particles of different specifications include alloy particles of specifications of 1mm-3mm, 3mm-5mm and 5mm-7mm.

8. The method for manufacturing a high-hardness, low-density ceramic alloy material for surface welding of well repair tools according to claim 2, characterized in that: The mold in S4 is a cylindrical mold with a diameter of 8mm-20mm.

9. The method for manufacturing a high-hardness, low-density ceramic alloy material for surface welding of well repair tools according to claim 2, characterized in that: The hardness of the polygonal ceramic alloy particles is HV1800-HV2000.

10. The method for manufacturing a high-hardness, low-density ceramic alloy material for surface welding of well repair tools according to claim 2, characterized in that: The sintering temperature in S3 is 1600±50° C., the sintering time is 8h±1h, and the furnace is cooled.